1998
DOI: 10.1074/jbc.273.15.8756
|View full text |Cite
|
Sign up to set email alerts
|

A Common Mechanism for the Interaction of Nitric Oxide with the Oxidized Binuclear Centre and Oxygen Intermediates of Cytochromec Oxidase

Abstract: The reactions of nitric oxide (NO) with fully oxidized cytochrome c oxidase (O) and the intermediates P and F have been investigated by optical spectroscopy, using both static and kinetic methods. The reaction of NO with O leads to a rapid (ϳ100 s ؊1 ) electron ejection from the binuclear center to cytochrome a and Cu A . The reaction with the intermediates P and F leads to the depletion of these species in slower reactions, yielding the fully oxidized enzyme. The fastest optical change, however, takes place w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
91
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 45 publications
7
91
0
Order By: Relevance
“…To fit the data in Fig. 2 A, this observation was taken into account, and the model of Antunes et al (43) was expanded to include an additional interaction at a noncompetitive site, consistent with previous observations that NO can react with the oxidized copper of the binuclear center, resulting in oxidation of NO to nitrite (25,26). Fig.…”
Section: Mode Of Inhibition: Simple Competitive Inhibition or More Comentioning
confidence: 99%
See 2 more Smart Citations
“…To fit the data in Fig. 2 A, this observation was taken into account, and the model of Antunes et al (43) was expanded to include an additional interaction at a noncompetitive site, consistent with previous observations that NO can react with the oxidized copper of the binuclear center, resulting in oxidation of NO to nitrite (25,26). Fig.…”
Section: Mode Of Inhibition: Simple Competitive Inhibition or More Comentioning
confidence: 99%
“…2). Note that, although a number of iron:oxygen intermediates (e.g., ferryl) are also likely to be present during turnover, the interactions of NO with these oxidized species (26,27) are formally included in the reaction step governed by k 1, and so this added complexity does not affect the conclusions drawn from this model. Additionally, the reaction step governed by k 2 is more complex than indicated because the nitrite dissociation rate depends on the redox state of the binuclear center (29 (43).…”
Section: Mode Of Inhibition: Simple Competitive Inhibition or More Comentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the use of a bacterial mutant in which the reduction of COX is very slow allowed researchers to observe the binding of NO to the single-electron-reduced Cu B ͞heme a 3 center (14), but whether this binding is effective in the wild-type protein remains unknown. Also recently, a mechanism for the inhibition of COX was proposed in which NO reacts with the oxidized form of Cu B , in which NO is initially oxidized, yielding nitrite (14)(15)(16). However, this inhibition is not competitive with oxygen and is not reversible by light as observed in cells, so it is generally accepted that the inhibition of COX by low physiological levels of NO involves binding, rather than reaction of NO with COX (6).…”
mentioning
confidence: 99%
“…More recent evidence has suggested that cytochrome c oxidase may provide a metabolic route for NO, either by interaction of NO with the reduced enzyme, leading to the formation of N 2 O, (18,19) or by interaction of NO with the oxidized enzyme, forming nitrite (NO 2 Ϫ ; 20,21). Although the NO reductase activity of the enzyme is too slow to constitute a physiological mechanism for the removal of NO (22), there is strong evidence in favor of the oxidation of NO to NO 2 Ϫ both by the purified enzyme (23,24) and by cells (25).…”
mentioning
confidence: 99%